Managing, Valuing, and Protecting Heritage Resources in the Twenty-First Century: Peatland Archaeology, the Ecosystem Services Framework, and the Kyoto Protocol. (August 2014) - Gearey, Benjamin R.; Fletcher, William; Fyfe, Ralph
<x content-type="archive" xml:space="preserve">Abstract</x> This paper argues that the development of the Ecosystem Services framework, which has recently emerged as an internationally recognized framework for valuing 'the 'natural capital' of ecosystems, presents a number of opportunities for heritage management and the archaeological record, arguing that the inclusion of archaeological and palaeoenvironmental 'value' within this framework presents an opportunity to incorporate heritage alongside a range of other critical 'services'. It presents a short case study focusing on the problems facing the preservation of peatland archaeological sites and deposits in situ alongside developments within peatland conservation and restoration initiatives partly driven by the ability of healthy, functioning peatlands to sequester carbon and hence mitigate climate change. It is argued that this drive towards peatland re-wetting may bring both positive benefits and opportunities for heritage management but also presents a number of practical issues, which now require active engagement from the archaeological community.